The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3389/fimmu.2013.00248
|View full text |Cite
|
Sign up to set email alerts
|

Sweeten PAMPs: role of sugar complexed PAMPs in innate immunity and vaccine biology

Abstract: Innate sensors play a critical role in the early innate immune responses to invading pathogens through sensing of diverse biochemical signatures also known as pathogen associated molecular patterns (PAMPs). These biochemical signatures primarily consist of a major family of biomolecules such as proteins, lipids, nitrogen bases, and sugar and its complexes, which are distinct from host molecules and exclusively expressed in pathogens and essential to their survival. The family of sensors known as pattern recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(122 citation statements)
references
References 195 publications
(245 reference statements)
0
115
0
1
Order By: Relevance
“…Based on these results, we suggest that PLE0 activates the TLR2/Myd88-dependent pathway as a TLR2 ligand and consequently enhances immune responses in IFN-␥-primed RAW 264.7 macrophages. It has been reported that TLR2 senses a number of polysaccharide types, such as lipoteichoic acid, teichoic acid, peptidoglycan, glycophosphatidylinositol anchored proteins, lipoarabinomannan, and arabinogalactan [49]. Unfortunately, because the characterization of glycosyl linkage in PLE0 remains to be elucidated, we could not identify the region recognized by TLR2.…”
Section: Discussionmentioning
confidence: 64%
“…Based on these results, we suggest that PLE0 activates the TLR2/Myd88-dependent pathway as a TLR2 ligand and consequently enhances immune responses in IFN-␥-primed RAW 264.7 macrophages. It has been reported that TLR2 senses a number of polysaccharide types, such as lipoteichoic acid, teichoic acid, peptidoglycan, glycophosphatidylinositol anchored proteins, lipoarabinomannan, and arabinogalactan [49]. Unfortunately, because the characterization of glycosyl linkage in PLE0 remains to be elucidated, we could not identify the region recognized by TLR2.…”
Section: Discussionmentioning
confidence: 64%
“…The molecular signature of pathogens, often referred to as pathogen-associated molecular patterns (PAMPs), is recognized by immune pattern recognition receptors (PRRs) on DCs. Sugar-complexed PAMPs 102 are the largest constituents of PAMPs and include lipopolysaccharide (LPS), N -acetylglucosamine (GlcNAc), peptidoglycan, and glucan-containing cell walls. Activation of PRRs results in the expression of antigen-presenting molecules (MHCII), co-stimulatory factors (CD80/86, CD40), and pro-inflammatory cytokines.…”
Section: Probing Glycan Functions In Innate Immunity With Glycomaterialsmentioning
confidence: 99%
“…In humans thirteen members of the Toll‐like receptors (TLR), family have been described. These are conserved membrane proteins which bind to components of bacteria, fungi and viruses as well as the damage‐associated molecular patterns (DAMPs) . Among TLRs, TLR‐9 recognizes unmethylated CpG dinucleotides expressed in bacteria and viruses and also vertebrate DNA.…”
Section: Introductionmentioning
confidence: 99%